PENGARUH PENGETAHUAN KEWIRAUSAHAAN DAN PELUANG KERJA DIBIDANG AKUNTANSI TERHADAP MINAT BERWIRAUSAHA - Satya Artha Pratama; Abdul Wahid Mahsuni; Siti Aminah Anwar (e_Jurnal Ilmiah Riset Akuntansi, 2020)
ABSTRACTThis study aims to determine the effect of entrepreneurial knowledge and job opportunities in the accounting sector on the interest in entrepreneurship. The population in this study were all accounting students of the 2017 Batch Year 2017 Islamic University Malang Program. The sample used is a portion of accounting students for the 2017 Undergraduate Program, Islamic University of Malang. The technique used in sampling is purposive sampling technique, the sample selected is 85 respondents. Data was collected using a questionnaire method. The data analysis method used is multiple regression analysis with the help of SPSS software version 14 (Statistical Products and Service Solutions version 14). The test data used are simultaneous hypothesis testing (f), determination coefficient (R2), and partial hypothesis testing (t). The results showed that the independent variable simultaneously had a significant effect on the dependent variable. Based on the coefficient of determination test results, the value of Adjusted R2 Square is 68.1% while the remaining 31.9% is influenced by other variables not included in this study. Based on the partial test results, all variables have an influence on Entrepreneurial Interest, Entrepreneurial Knowledge (sig = 0,000) and Job Opportunities (sig = 0,000) have an effect on Entrepreneurial Interest. Keywords: Entrepreneurial Knowledge, Job Opportunities in Accounting and Entrepreneurial Interest